Mergers Advisors Impact on M&A Success: Canadian Evidence - Nabiyou, Romaric (Université d'Ottawa / University of Ottawa, 2020)
This paper investigates the impact of advisors on the success of Canadian firms’ mergers and acquisitions. Using a sample of 791 deals from Canadian TSX listed acquiring firms from 2001 to 2015, we first investigate what types of firms hire advisors and top advisors in particular. Second we investigate two important hypotheses of mergers advisors role: (a) the superior deal hypothesis, which expects the improvement in firm performance after the support of an advisor; and, (b) the deal completion hypothesis, which expects higher completion rates and speed for advisor-backed acquirers. In summary, we found little support for the superior deal hypothesis. The short-term performance of an advisor-backed acquirer was significantly higher than that of non-advisor-backed acquirer only when the target has no advisor. The acquirer’s CAR was worst when both parties (acquirer and target) had an advisor. In addition, we saw no evidence that acquirers with top advisors generate higher short-term returns than those with lower tier advisors. When investigating the long-term performance, we do not find any significant evidence that advisors positively impacted value for acquirers. The same conclusion holds for the completion hypothesis as we discovered that advisors have no impact on the time to completion. All the analyses controlled for acquirer, target, and deal characteristics.
Keywords: Mergers; Acquisitions; Advisors; Canada